MUSIC USE IN MEDICINE: A PREVIEW: चिकित्सा के क्षेत्र में संगीत का प्रयोग: एक संक्षिप्तावलोकन - Gandhi, Alapparani (International Journal of Research -GRANTHAALAYAH, 2015)
Music is an art that affects not only the conscious but also the roots. Music not only gives pleasure, but is also indicative of the mental state of man or creature and also affects our emotions. The inclusion of tone and tempo in music affects our soul. Human actions are also dynamic because of the resemblance between the two, the raga raagnis affect our soul and body. The power of raga and rhythm comes due to their regularity. It is the nature of man’s behavior that we are more affected by regularity or harmony than by balancing imbalance, order in chaos, and reconciliation. Therefore, we can say that restraint and harmony of tone and rhythm affect us. संगीत एक ऐसी कला है जिससे न केवल चेतन अपितु जड़ भी प्रभावित होता है। संगीत केवल आनंदानुभूति ही नहीं देता वरन् मनुष्य या प्राणी की मानसिक स्थितियो की भी सूचक होता है और हमारे मनो भावों को भी प्रभावित करता है। संगीत मे स्वर व गति (लय) का समावेश हमारी आत्मा को प्रभावित करता है। मानवीय क्रियाए भी गत्यात्मक होती है दोनों मे सादृश्यता होने के कारण ही राग रागनियाँ हमारी आत्मा और शरीर को प्रभावित करती है। राग और लय की शक्ति इनकी नियमितता के कारण ही आती है। यह मनुष्य का स्वभावगत व्यवहार है कि असंतुलन में संतुलन, अव्यवस्था में व्यवस्था और असामंजस्य में सामंजस्य लाने की अपेक्षा नियमितता या स ंयम से हम अधिक प्रभावित होते है। अतः हम यह कह सकते है कि स्वर एवं लय का संयम तथा सामंजस्य ही हमें प्रभावित करता है।